Significant improvements in cataract treatment and persistent inequalities in access to cataract surgery among older Poles from 2009 to 2019: results of the PolSenior and PolSenior2 surveys - Natalia Lange; Hanna Kujawska-Danecka; Adam Wyszomirski; Klaudia Suligowska; Klaudia Suligowska; Adrian Lange; Dorota Raczyńska; Justyna Jędrychowska-Jamborska; Małgorzata Mossakowska (Frontiers Media S.A., 2023)
Background and aimsCataract is the leading cause of visual impairment and blindness among older adults worldwide, that can be corrected through surgical interventions. However, diagnosis and treatment bias can be observed, and it is a major issue for improving health policies. Therefore, we assessed a declared prevalence of cataract and the frequency of surgical treatment of this condition in the Polish population in the years 2009-2019. To provide evidence of health inequalities, we compared operated and non-operated seniors using selected socioeconomic factors and identified variables affecting the availability of cataract surgery services over a 10-year follow-up period.MethodsAn analysis based on a survey among 4,905 participants of the nationwide PolSenior study conducted in 2008-2009, and 5,031 participants of PolSenior2 conducted one decade later to assess the health of Poles over 65 years of age.ResultsCataract diagnosis was declared by 25.5 and 28.2% of the study population in PolSenior and PolSenior2 surveys, respectively. Out of those diagnosed with cataract in PolSenior, 46.5% underwent surgical treatment for at least one eye. This rate increased up to 67.9% in the survey conducted 10 years later. Independent factors increasing the chance for cataract surgery in both cohorts included male sex and age > 75 years. Additional factors were self-reported good health status in PolSenior and lack of financial problems in purchasing medicines in PolSenior2. Over the investigated decade, the chances for cataract surgical treatment increased in single-living and widowed patients. The shortage of funds for medications remained the only significant barrier for surgery.ConclusionAlthough the prevalence of cataract in the older adult population in Poland has not changed from 2009 to 2019, the rate of cataract surgeries has considerably increased over the analyzed decade. Patients with lower socioeconomic status and women have lower access to surgical cataract management.